(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article researches how the metaphorical picture of the world is often portrayed through the names of animals in various contexts. The world is closely connected with the names of animals that surround it. From this point of view, the use of the names of the animals in human speech as part of language units, that is, as part of phraseological and paremiological units, has been scientifically researched.